Internal combustion engine handbook : basics, components, systems, and perspectives - Van Basshuysen, Richard, 1932-; Schäfer, Fred (SAE International, 2004)
Historical review - Characteristics - Maps - Thermodynamic fundamentals - Crank Gears - Engine components - Lubrication - Friction - Charge cycle - Supercharging of internal combustion engine - Mixture formation and related systems - Ignition - Combustion - Combustion systems - Electronics and mechanics for engine management and transmission shift control - The powertrain - Sensors - Actuators - Cooling of internal combustion engines - Exhaust emissions - Operating fluids - Filtration of operating fluids - Calculation and simulation - Combustion diagnostics - Fuel consumption - Noise emissions - Alternative propulsion systems - Outlook.